Authoring a dialogical working knowledge: A bakhtinian approach - Ahmad, Che Mahzan (Journal of International Social Research, 2009)
Nonaka’s (1991) theory on knowledge creation in organization in recent years has attracted a lot of interests among scholars. However notes about no satisfactory answer to the question what are the generative mechanisms through which new working knowledge is created continue to reverberate in many discussions and meetings. With the above puzzlement, this article gazes at dialogism for enlightenment. Dialogical encounters are seen as one of the key principal of authoring that enables new working knowledge to emerge. In taking this position of authorship, the notion of the dialogical paradigm that celebrates the dialogical model of reason is presented. This article is largely informed by Bakhtin’s.